Development of Tolerance and Peace Loving Character Assessment Instrument for Vocational High School Students - Komang Niti Widianti; I Ketut Gading; Ni Ketut Suarni (Bisma The Journal of Counseling, 2022)
This study aims to describe the tolerance and peace-loving character assessment instruments for vocational high school students. This research uses the Research & Development (R&D) method using the Borg and Gall method which has been adapted by Sugiyono. However, this study only used seven stages, namely: potentials and problems, data collection, product design, design validation, design revision, product testing, product revision. Instrument validity analysis was assisted with the help of Microsoft Excel. Reliability test using Alpha Cronbach formula. Based on the analysis, it is known that the reliability test results for the tolerance character instrument are 0.88 which indicates that the instrument used is reliable, as well as the peace-loving character assessment instrument. So it is recommended for teachers to use a peace-loving character assessment instrument for vocational high school students.